Perturbating Upper Semi-fredholm With Strictly Singular Operators - Galaz-Fontes, Fernando (Sarajevo Journal of Mathematics, 2024)
Given an upper semi-Fredholm operator $L$, following the work of P. Cassaza and N. Kalton [1] and others, we introduce and study a set of upper semi-Fredholm operators having the same index as $L$ and which is invariant under strictly singular perturbations. 2000 Mathematics Subject Classification. 47A53, 47A55